Kajian Teologis Terhadap Markus 10:17-27 - Mariduk Tambun; Adi Putra (JURNAL LUXNOS, 2019)
Abstract: This research is about theological studies on Mark 10: 17-27. The research was conducted to find out about the concept of the Kingdom of God contained in it. That is why researchers used a qualitative approach with literature review to examine this topic. As a conclusion from this research, several things are obtained, namely: it is found that the strong theological message in this passage is about the concept of the Kingdom of God. The concept of the Kingdom of God has become central to the mission and ministry of Jesus while on this earth. That is why the Canonical Gospels also make it a major theological issue in their gospel account. That is why in this passage, Jesus linked God's Kingdom with eternal life. Because the kingdom of God is about the salvation of sinful humans. The concept of the Kingdom of God in Mark 10: 17-27 is understood in three main topics, namely: The Kingdom of God means salvation, the Kingdom of God is not obtained through good deeds, and the kingdom of God concerns the suggestion that we love God more than humans. Abstrak: Penelitian ini tentang kajian teologis terhadap Markus 10:17-27. Penelitian dilakukan untuk mengetahui tentang konsep Kerajaan Allah yang termaktub di dalamnya. Itulah sebabnya, peneliti menggunakan pendekatan kualitatif dengan kajian pustaka untuk meneliti topik ini. Sebagai kesimpulan dari penelitian ini diperoleh beberapa hal yakni: dijumpai bahwa pesan teologis yang kuat dalam perikop ini adalah tentang konsep Kerajaan Allah. Konsep Kerajaan Allah memang menjadi sentral dalam misi dan pelayanan Yesus selama di bumi ini. Itulah sebabnya, Injil Kanonik pun menjadikannya sebagai isu teologis utama dalam catatan injil mereka. Itulah sebabnya dalam perikop ini, Yesus menghubungkan Kerajaan Allah dengan hidup kekal. Karena kerajaan Allah adalah menyangkut tentang keselamatan manusia yang berdosa. Konsep Kerajaan Allah dalam Markus 10:17-27 dipahami dalam tiga topik utama, yakni: Kerajaan Allah berarti tentang keselamatan, Kerajaan Allah diperoleh bukan melalui perbuatan baik, dan kerajaan Allah menyangkut tentang anjuran supaya kita lebih mengasihi Allah dari pada manusia.